PERLINDUNGAN PEKERJA PEREMPUAN DALAM KEBIJAKAN RAMAH KELUARGA DI TEMPAT KERJA: SOSIALISASI PADA SERIKAT PEKERJA - Amriyati Amriyati; Siti Nurbaiti; Ning Adiasih; Septiyani Septiyani; Meta Indah Budhianti; Arini Suliantari; Fraya Layola Nainggolan (Jurnal Abdimas Bina Bangsa, 2023)
The Basic Law protects the right to employment and proper treatment, in accordance with relevant international instruments. Laws and regulations harmonize it and this is related to family-friendly policies, as a form of protection for women workers. However, not all rights of women workers have been fulfilled due to limited knowledge and other wills and interests. Trade unions are entrusted with fighting, improving the welfare of workers / workers and their families responsibly. The purpose of this Community Service is to socialize to partners: how to describe the protection of women workers, especially in Indonesia; Description of family-friendly policies as well as examples of their implementation. Material preparation is carried out through literature studies. The implementation was carried out in a hybrid manner using zoom and participants from the trade union gathered in the meeting room of the Bekasi trade union office, the PKM team gathered in the meeting room of the Faculty of Law Usakti. Evaluation of activities is carried out after exposure to the material through 4 related questions. The post-test results  showed an increase in the knowledge of SP administrators about: understanding family-friendly policies; the benefits of family-friendly policies for both workers and employers. The results of PKM preparation in the form of studies show that the protection of women workers has been outlined in laws and regulations. Family-friendly policies balance work and family life, including: maternity leave, availability  of day care at work,  breastfeeding opportunities at work time, implementation of work outside the workplace for certain types of work that allow. Policies result from the cooperation of HRD, SP, government and community. The support of supervisors and managers is critical to the success of family-friendly policies. It is suggested that trade unions play a lot of role in the formation and implementation of family-friendly policies.